The Maranao Streamers and Tarpaulins as Tools of Communication: An Ethnographic Study - Monara Hamiydah M. Maruhom (Philippine Association of Institutions for Research, Inc., 2015)
An organization is a conglomeration of individual cultural practices and not just a system of human beings acting and interacting with one another in their society. Understanding the Maranao practice of displaying streamers locally called bidangan and tarpaulin provides people with a better picture of how these cultural practices affect their way of life. The study aimed mainly to comprehend the history and origin of this set of flags. Participant-observation qualitative technique was employed to closely observe how the streamers are displayed for various occasions. Personal random interviews were conducted to individuals who are knowledgeable on the subject matter. The study found that the Maranao folk have continued to maintain their native culture, traditions, customs and way of life. The results of this study will serve as a basis for developing a policy framework to educate the Maranao society on the proper use of streamers in the preservation of their remarkable traditional culture.